OP65 What's Best for Mental Health: No Job or Any Job at All?. (10th September 2013) - McManus, S; Butterworth, P; Leach, L; Stansfeld, S
Abstract : Background: In terms of mental health, employment is generally better for people than joblessness. But is that still the case when the choice is between unemployment and a demanding job with low levels of control, security and reward? The prevalence of psychiatric disorders among people who are unemployed has rarely been compared with those in jobs of differing psychosocial quality. Methods: The Adult Psychiatric Morbidity Survey (APMS) was commissioned by the NHS Information Centre, with funds from the Department of Health. It is a probability sample general population survey, from which the rates of treated and untreated mental illness in England are derived. Participants' mental health is assessed using the Clinical Interview Schedule (CIS-R), a validated assessment tool operationalising criteria for anxiety and depressive disorders, as specified in the International Classification of Diseases 10. In the 2007 survey, we included a module covering the Job Strain and Effort-Reward Imbalance models of work-related stress. Quality of work was assessed by the number of adverse psychosocial job conditions reported (high demands, and low control, security and esteem). We examined prevalence and risk of common mental disorders (CMDs) among the 2603 participants aged 21 to 54 years who were either (i) unemployed and looking for work at the time of interview, or (ii) employed (in jobs banded by their psychosocial quality). Results: A logistic regression model adjusted for age, sex, partnership status, debt and housing conditions was run to produce ORs for CMD. They were 0.16 ([95% CI 0.10, 0.26], p < 0.001) for people employed the highest quality jobs and 0.79 ([0.41, 1.54], p = -0.492) among unemployed people, compared with employees in the poorest quality jobs. Conclusion: While people who are unemployed or in low quality work have worse mental health than those in high quality work, jobs of poor psychosocial quality may be no better for mental health than being unemployed. Getting the jobless back into work is, of course, a priority for recession-hit Britain. But so are the Government's plans to improve national wellbeing. These results highlight the relevance of what goes on in the workplace for the wellbeing agenda, and show that policies aimed at increasing the employment rate should not be at the expense of job quality.